Journalists' Normative Constructions of Political Viewpoint Diversity. (26th April 2018) - Vos, Tim P.; Wolfgang, J. David
Abstract : This in-depth interview-based study with US political journalists explores how they conceptualize the portrayal of political viewpoint diversity as a journalistic norm, particularly in light of changes to news and the news media ecology. The political journalists still discursively embrace the normative role of providing audiences with a range of political viewpoints, but express assumptions about democracy that seem to thwart their intentions. The implications for the journalistic field and field theory are considered.